Illumination Intelligent Adaptation and Analysis Framework: A comprehensive solution for enhancing nighttime driving fatigue monitoring - Nur Safinas binti Albakry (Tanjung Malim, 2024)
Illumination Intelligent Adaptation and Analysis Framework: A comprehensive solution for enhancing nighttime driving fatigue monitoring by Nur Safinas binti Albakry